Intestinal oligopeptide transporter PepT1-targeted polymeric micelles for further enhancing the oral absorption of water-insoluble agents. Issue 44 (4th November 2019) - Jin, Yao; Liu, Qi; Zhou, Chuhang; Hu, Xinping; Wang, Leqi; Han, Shidi; Zhou, Yuanhang; Liu, Yan
Abstract : Intestinal transporter PepT1-targeted polymeric micelles were fabricated as nanocarriers for further enhancing the oral absorption of water-insoluble agents via PepT1-mediated transcytosis. Abstract : The intestinal epithelium is the main barrier for nanocarriers to orally deliver poorly water-soluble and absorbed agents. To further improve the transmembrane transport efficiency of polymeric micelles, intestinal oligopeptide transporter PepT1-targeted polymeric micelles were fabricated by Gly-Sar-conjugated poly(ethylene glycol)-poly(d, l -lactic acid). The functionalized polymeric micelles with about 40 nm diameter, uniform spherical morphology and favorable cytocompatibility with Caco-2 cells were demonstrated to distinctly enhance the cellular uptake and transmembrane transport of the loaded agents. The results of intestinal absorption strongly evidenced the higher accumulation of the micelles inside the epithelial cells, at the apical and basolateral sides of the epithelium within the villi in mice. Furthermore, the interaction of Gly-Sar decorated polymeric micelles with PepT1 was explored to promote the internalization of the micelles through fluorescence immunoassay, and the PepT1 level on the membrane of Caco-2 cells treated with the micelles appeared to change in a distinctly time-dependent manner. Both clathrin- and caveolae-mediated pathways were involved in the transcellular transport for undecorated polymeric micelles, while the transcellular transport pathway for Gly-Sar decorated ones was changed to be mainly mediated by clathrin and lipid rafts. The colocalization of Gly-Sar decorated micelles with the organelles observed by confocal laser scanning microscopy indicated that late endosomes, lysosomes, endoplasmic reticulum and Golgi apparatus appeared to participate in the intracellular trafficking progression of the micelles. These results suggested that PepT1-targeted polymeric micelles might have a strong potential to greatly promote the oral absorption of poorly water-soluble and absorbed agents.